Resilience of temperate peatland vegetation communities to wildfire depends upon burn severity and pre‐fire species composition - Davies, G. Matt; Gray, Alan; Power, Simon C.; Domènech, Rut (Ecology and evolution, 2023)
Peatland ecosystems are of global conservation and environmental importance storing globally significant amounts of ancient carbon, regulating regional temperatures and hydrological regimes, and supporting unique biodiversity. Livestock grazing, land‐use change, drainage, nutrient and acid deposition, and wildfire threaten the composition and function of many peatlands including those in the uplands of the United Kingdom. Presently, little is known about either the short‐ or long‐term effects of wildfires within these systems in the UK. Our study aimed to evaluate how plant communities respond to wildfires across a range of vegetation communities, soil types, and burn severities. We evaluated wildfire burn severity using the ground‐based Composite Burn Index adapted for treeless peatlands. Using paired burned–unburned plots, we quantified differences in the abundance of plant families and functional groups, vegetation diversity, and community composition. Multivariate differences in composition between burned and unburned areas were used as an index of community resilience to fire. Plots in heathland communities with shallow organic soils burned at the highest severities and had the greatest reductions in plant diversity and richness. There were significant declines in plot‐scale species richness and diversity with increasing burn severity. Graminoids were resilient to fire whilst Ericaceae tended to increase with higher severity. Bryophyte composition was substantially altered—pleurocarpous species declined and acrocarpous species increased with greater burn severity. Community resilience was related to ground layer burn severity with higher burn severity driving greater changes in communities. Wildfire effects on temperate peatlands are a function of fire weather and site environmental and ecological characteristics. Management policy should ensure that the risk of severe wildfires is mitigated to protect ecosystem function and biodiversity. This will require system‐specific fire management prescriptions across the gradient of peatland soil and vegetation types. Peatland wildfires are expected to be a growing problem under climate change, but we have little knowledge of how temperate systems respond to varying fire severity. We investigated differences in the diversity and composition of paired burned and unburned areas across five wildfires in the United Kingdom that burned at differing severities. Plant community diversity and resilience were significantly associated with both burn severity and community type with most differences occurring among cryptogams.